ANALISIS STRES KERJA KARYAWAN BESERTA FAKTOR PENYEBAB DAN CARA MENGATASINYA - Zuhrotul Maghfiroh; Yacobo P Sijabat (Parsimonia - Jurnal Ekonomi dan Bisnis, 2021)
Stress is a common thing for workers because of the workload, job satisfaction, causing stress for employees. A task that is seen as challenging by one person can result in high levels of anxiety in another. When people are emotional, employees develop a variety of stress symptoms that can worry their performance and health, and even impair their ability to cope with the environment. So there needs to be good communication between employees and managers to relieve stress on employees in this case managers and companies have a big influence on stress on employees, the method used is literature study by searching on several websites, namely Google Schoolar, CiteSeerX, Neliti, and Elsevier with a cross sectional research design. The purpose of this article is to determine the factors that influence employee work stress. From the article review, it can be seen that work stress can occur due to pressure on workers, causing poor performance, decreased job satisfaction and employee turnover invention. The cause of stress is also due to environmental factors and organizational factors for that attention is needed to reduce work stress.